KAJIAN HUKUM TENTANG POLITIK UANG DALAM KAMPANYE MENJELANG PEMILIHAN UMUM: Legal Study On Money Politics In Campaigns Ahead Of General Elections - Muhamad Ruslan (Yayasan Al-Amin Qalbu, 2025)
Money politics in election campaigns is one of the main issues in the practice of democracy in Indonesia. This phenomenon creates bias in the implementation of the principles of justice, freedom, and honesty in general elections. This article aims to analyze the legal aspects related to money politics in campaigns leading up to elections, including applicable laws and regulations, their implementation, and their social and political impacts. This study uses a qualitative descriptive method with a normative approach that refers to laws and regulations such as Law Number 7 of 2017 concerning Elections. The results of the study show that although regulations have been in place, the practice of money politics is still a major challenge that requires stricter supervision and law enforcement